Volver : país de salida : Venezuela : manual de proceso (2018)
The traditional definition of diaspora is understood as a population that cannot return to their homeland due to multiple circumstances. In this book I do not refer to a physical return but to a symbolic one that corresponds to how Venezuelan migrants, under the circumstance of diaspora, transform and build new spaces to feel at home again. Through this book it is possible to explore some processes of adaptation and cultural hybridity of these migrants in their new countries from home spaces and objects that are part of their daily life. In this way I show how migrants become bridges between two worlds and individuals that, with the pass of the time and according to their adaptation process, are capable of accepting two cultures at the same time. This acceptance of two cultures is what makes them "from here and there" but, at the same time, it is what helps...